2002
DOI: 10.2355/isijinternational.42.588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Surface Tension and Adsorption for Liquid Fe-S Alloys.

Abstract: Surface tension of liquid iron is strongly influenced by the adsorption of sulfur. In this study, surface tensions of liquid Fe-S alloys at 1 823 K were measured by the sessile drop technique in a purified argon atmosphere. Experimental results were compared with the model based on Butler's equations considering the effect of size and interactions of the adsorbed elements assuming that the system was composed of Fe-"FeS" binary. The model could evaluate the surface tension and the adsorption of sulfur more rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…14,17,18) This method has already been applied to various alloy and slag systems by the authors with succeed. 15,16,[19][20][21][22][23][24][25][26][27] As shown in Fig. 3, the agreement between calculations (solid line) and measurements (solid circles) in the present work is also reasonable.…”
Section: Surface Tension Of Liquid Ag-sn Alloyssupporting
confidence: 74%
See 1 more Smart Citation
“…14,17,18) This method has already been applied to various alloy and slag systems by the authors with succeed. 15,16,[19][20][21][22][23][24][25][26][27] As shown in Fig. 3, the agreement between calculations (solid line) and measurements (solid circles) in the present work is also reasonable.…”
Section: Surface Tension Of Liquid Ag-sn Alloyssupporting
confidence: 74%
“…Many researchers have shown that the minimum area occupied by single oxygen atom at saturation on the surface of metal M is close to those for oxide compound M n O. 2,9,26,27,30,31) If we assume Ag 2 O structure is formed on the surface of liquid silver as suggested by Bernard and Lupis,9) the minimum areas occupied by single oxygen atom on (100) and (111) faces, respectively, equal to 0.32 and 0.38 nm 2 , which are very close to the present result (0.36 nm 2 ). On the other hand, the minimum area occupied by single oxygen atom in the surface of pure tin and Ag-Sn alloys are much larger than that of pure silver.…”
Section: Effect Of Oxygen On Surface Tension Of Liquid Ag-sn Alloysmentioning
confidence: 99%
“…6 63) investigated positive temperature coefficients for Fe-based alloy systems containing surface active elements such as sulfur and oxygen, yielding very positive excess free energies. 5,7) For liquid alloys having a negative excess free energy, however, it has not been clarified whether the positive temperature coefficient be found. Moser et al 12) observed negative temperature coefficients for liquid Sn-Ag alloys, but they pointed out that the predicted values by thermodynamic calculations showed positive temperature coefficients in the concentration range of 30 $ 60 at% Sn at the lower.…”
Section: Temperature Coefficientmentioning
confidence: 99%
“…Many researchers including the authors have shown that the surface tension of liquid alloys can be predicted by Butler's model using thermodynamic database within experimental errors. [2][3][4][5][6][7][8][9][10][11][12] Using Butler's model, the temperature coefficient of surface tension (d'=dT) for liquid alloys can also be obtained by calculating the surface tension with changing temperature at a fixed composition. Generally, the temperature coefficients of liquid metals and alloys are negative.…”
Section: Introductionmentioning
confidence: 99%
“…For the S-bearing system, we adopt the activity model for the Fe-FeS binary determined at ambient pressure by Lee & Morita (2002), assuming no significant pressure effect on their activity coefficients. For comparison we also estimate the oxygen fugacities of our experiments by using the activity model of Asahara et al (2004).…”
Section: (B ) Oxygen Fugacitymentioning
confidence: 99%